Challenges and strategies for improving education quality through teacher supervision - Putra, M. Jaya Adi; Hendro, Jhon; Utari, Nadia (Universitas Negeri Padang, 2025)
This study aims to examine the role of educational supervision in improving the quality of learning in Vocational High Schools (VHS), focusing on the challenges faced and strategies to optimize its implementation in vocational education. Educational supervision is very important in supporting the professionalism of Vocational High Schools teachers, the effectiveness of school management, and improving the quality of learning that integrates vocational theory and practice. The research method used is a literature study, by reviewing scientific journals, books, and research reports related to VHS. The results of the study show that supervision carried out in a systematic, planned and sustainable manner can encourage teachers' professional growth and significantly improve the quality of vocational education. However, the implementation of supervision in Vocational High Schools still faces obstacles such as limited competence of supervisors in vocational fields, high administrative burden of teachers, and lack of structural support and resources. To overcome these obstacles, the study proposes strategies such as collaborative-based supervision between teachers and supervisors and the utilization of information technology for monitoring and evaluation. The findings are expected to provide practical contributions for policy makers, school supervisors and educators in developing educational supervision that is effective, relevant and has a positive impact on the quality of learning in Vocational High Schools.